Cigarette smoking in childhood and risk of all-cause and cause-specific mortality in adulthood - Xue Liu; Jiahong Sun; Min Zhao; Pascal Bovet; Bo Xi (Frontiers Media S.A., 2023)
BackgroundThis study was aimed to examine the association between cigarette smoking in childhood and mortality in adulthood, and the impact of non-smoking duration among smokers who subsequently quit smoking.MethodsWe used data from 472,887 adults aged 18-85 years examined once in the US National Health Interview Survey in 1997-2014, which was linked to mortality data from the National Death Index up to 31 December 2015. Cigarette smoking status in childhood (age 6 to 17 years) and adulthood (age 18 to 85 years) was self-reported using a standard questionnaire at the time of participation in the survey. The vital status of participants due all-causes, cardiovascular disease (CVD), cancer and chronic lower respiratory diseases was obtained using mortality data from the National Death Index.ResultsDuring the mean follow-up of 8.75 years, compared with never smoking in childhood and adulthood, the risk of all-cause mortality among current adult smokers decreased slightly according to increasing age at smoking initiation: hazard ratios (HRs; 95% confidence intervals, CIs) were 2.54 (2.24-2.88) at age of 6-9 years, 2.44 (2.31-2.57) at age of 10-14 years, and 2.21 (2.12-2.31) at age of 15-17 years. Smoking cessation before the age of 30 years was not associated with increased risk of all-cause and cause-specific mortality (all p > 0.05) compared to never smoking.ConclusionMortality risk was higher in individuals who started smoking at an earlier age in childhood. Inversely, smoking cessation before the age of 30 years was not associated with an increased risk of mortality compared to never smoking.